Mitochondrial respiratory chain dysfunction in a patient with a heterozygous de novo CTBP1 variant. Issue 6 (24th August 2022) - Wong, Wui‐Kwan; Balasubramaniam, Shanti; Wong, Rachel S. H.; Graf, Nicole; Thorburn, David R.; McFarland, Robert; Troedson, Christopher
Abstract: The C‐terminal binding protein 1 (CTBP1) functions as a transcriptional corepressor in vertebrates and has been identified to have critical roles in nervous system growth and development. Pathogenic variants in the CTBP1 gene has been shown to cause hypotonia, ataxia, developmental delay and tooth enamel defect syndrome (HADDTS). There have only been 16 cases reported to date with heterozygous, pathogenic variants in CTBP1 manifesting with a neurodevelopmental phenotype. We report a further case of a pathogenic, heterozygous, de novo variant in CTBP1 identified by whole exome sequencing in a female with the typical phenotype of global developmental delay, hypotonia, cerebellar dysfunction and failure to thrive. Additionally, muscle biopsy demonstrates evidence of a respiratory chain defect, only previously reported once in the literature. This supports the role of CTBP1 in maintenance of normal mitochondrial activity and highlights the importance of considering secondary mitochondrial dysfunction in genes not directly involved in the mitochondrial respiratory chain.